1988
DOI: 10.1021/ic00292a011
|View full text |Cite
|
Sign up to set email alerts
|

Heterobimetallic gold-osmium and gold-ruthenium hydrido complexes. X-ray crystal and molecular structures of [Au2Os(H)3(PPh3)5]PF6 and [AuRu(H)2(CO)(PPh3)4]PF6

Abstract: Several new heterobimetallic hydrides containing gold have been synthesized. [Au2Os(H)3(PPh3)5]PF6 (1) was made by the reaction of AuPPh3NQ3 and Os(H)4(PPh3)3 with CH2C12 as solvent. [Au2Ru(H)3(PPh3)5]PF6 (2) was synthesized in an analogous manner from AuPPh3NQ3 and Ru(H)4(PPh3)3 with toluene as solvent. [AuRu(H)2(CO)(PPh3)4]PF6 (3) and its osmium analogue, [AuOs(H)2(CO)(PPh3)4]PF6 (4), and [AuOs(H)2(CO)2(PPh3)3]PF6 (5) and its ruthenium analogue, [AuRu(H)2(CO)2(PPh3)3]PF6 (6), were prepared by the reaction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 11 publications
(15 reference statements)
2
7
0
Order By: Relevance
“…In the gold complex 8a (Figure ) there is no exopolyhedral B−H⇀Au bond supplementing the Ru( μ -H)Au linkage [Ru−Au 2.7205(8) Å, Ru−H(001) 1.79(6) Å, Au−H(001) 1.37(5) Å]. These distances compare well with those found in the cation [RuAu( μ -H) 2 (CO)(PPh 3 ) 4 ] + [Ru−Au 2.786(1) Å, Ru−H 1.78(4) Å, Au−H 1.61(4) Å] . The absence of an agostic B−H⇀Au interaction in 8a and the presence of the B−H⇀Cu linkage in 7a can be related to the relative differences in the energies of the unoccupied frontier orbitals in the fragments M(PPh 3 ) (M = Cu or Au).…”
Section: Resultssupporting
confidence: 66%
“…In the gold complex 8a (Figure ) there is no exopolyhedral B−H⇀Au bond supplementing the Ru( μ -H)Au linkage [Ru−Au 2.7205(8) Å, Ru−H(001) 1.79(6) Å, Au−H(001) 1.37(5) Å]. These distances compare well with those found in the cation [RuAu( μ -H) 2 (CO)(PPh 3 ) 4 ] + [Ru−Au 2.786(1) Å, Ru−H 1.78(4) Å, Au−H 1.61(4) Å] . The absence of an agostic B−H⇀Au interaction in 8a and the presence of the B−H⇀Cu linkage in 7a can be related to the relative differences in the energies of the unoccupied frontier orbitals in the fragments M(PPh 3 ) (M = Cu or Au).…”
Section: Resultssupporting
confidence: 66%
“…While the origin of the enhancement by gold (but not by copper) is not known, these results strongly support catalysis by intact clusters.226 Other mixed-metal ruthenium-gold clusters catalyze olefin isomerization as well. 321 A mixed-metal Ni-Ru cluster, CpNiRu3(n-H)3(CO)9, selectively catalyzes hydrogenation and isomerization of double bonds. The presence of both metals is important in the catalysis, indicating cluster catalysis.…”
Section: Isomerizationmentioning
confidence: 99%
“…This strategy has been extended to other transition metals such as Nb, [25] Ru, [26] Os. [27] More recent studies revealed that these species might turn into interesting catalytic systems; for example, Crimmin reported that heterobimetallic copper-gold hydrides can hydroborate CO2 in the presence of pinacolborane in high selectivity to give formate derivatives. [28] From a mechanistic point of view, Au-H-M moieties can be seen as a situation where the hydride transfer is arrested in an intermediate stage.…”
Section: Introductionmentioning
confidence: 99%